College Student Self-Efficacy in Information Literacy: Influence On Their Research Academic Skills (British Journal of Multidisciplinary and Advanced Studies, 2023)
Self-efficacy in information literacy refers to the individual's confidence in his ability to locate, evaluate, and use information to accomplish a goal. This concurrent nested mixed method explored the college students’ self-efficacy in information literacy in relation to their research academic skills. There were 81 fourth-year college students enrolled in the program of Bachelor of Science in Information Technology in a satellite campus of a state university in Misamis Oriental. The instrument’s validity and reliability were ensured through panel review and reliability test using the Cronbach’s alpha. Data were analyzed using descriptive statistics and multiple regression analysis. Findings reveal that participants’ research academic skills were generally very good, indicating that they performed well on their capstone research project and their self-efficacy on information literacy skills were generally all high. Self-efficacy in information literacy skills in terms of synthesizing and creating significantly influenced the research academic skills. Strengthened research capability emerged as the theme which contributed good in academic research skills. It was concluded that students who had high self-efficacy in information literacy skills were more likely to feel confident in their ability to conduct effective research and use information effectively, thus contributing to effective research academic skills. This study points the need to develop and implement innovative information literacy programs.